Uji Aktivitas Hipoglikemik Kombinasi Sirsak (Annona muricata) Dan Kelor (Moringa oleifera) Pada Tikus Diabetes Mellitus Yang Diinduksi Aloxan Activity test of Hypoglycemic of combination of sourson (Annona muricata) and moringa (Moringa oleifera) in Mi - Hartono .; Agil Novianto - STIKES Nasional Surakarta (Indonesian Journal on Medical Science, 2017)
Abstract: Increase level of glucose can lead oxidative sress which is sign by anormaly level of free radical on the body. Research from the past, soursop and moringa extract can reduce glucose level on the single dose.The study was conducted to determine the dose of optimal from a combination of extracts ethanol leaves soursop and moringa  more effective decrease of blood glucose levels in male mice wistar strain induced alloxan as compared to the provision of a single.The test as much as 36 mouse that were divided into eight groups, namely : normal, negative (CMC-Na), positive (glibenklamid), soursop extract 100 mg/bw (S 100), moringa extract 200 mg/bw (K100), SK 75:25, SK 50:50 and SK 25:75. All the test animals, except the normal induced aloxan on the day zero, followed by the test animals of the day 1st to 14th day. The data collected in the form of blood sugar levels of serum taken on the day zero, the 7th day and the 14th day and be measured using the method of GOD-PAP and measured of glucose level and analyzed to ge % hypoglycemic level. All data then analyzed with ANOVAextrac (Analysis of Varians) with (α = 0,05). A combination of extracts soursop and moringa  extract more effectively decreasing blood glucose levels significantly (p<0,05). Both extract single or combination can reduce glucose level. Dosages of optimal from a combination of extracts soursop and moringa  extract to decrease blood glucose levels, doses SK 50:50  with the percentage of a hypoglycemic level by 36,56 %> This combination more effectively decreasing blood glucose levels compared to each  single dose.Key word: sourson, morina, diabetic mellitus, aloxan Abstrak: Kenaikan kadar gula dalam darah akan memicu terjadinya kondisi stress oksidatif yang ditandai dengan ketidakseimbangan antara jumlah radikal bebas dan antioksidan. Penelitian yang terakhir dilakukan ekstrak sirsak dan kelor efektif untuk menurunkan kadar gula dalam darah namun penelitian yang ada masih dilakukan dalam bentuk tunggalnya dan belum pernah dilakukan kombinasi antar kedua ekstrak. Penelitian ini dilakukan untuk mengetahui pengaruh kombinasi ekstrak sirsak dan kelor terhap kadar glukosa pada tikus yang diinduksi aloxan. Hewan uji sebanyak 36 ekor yang dibagi menjadi 6 kelompok yaitu: kelompok normal (aquadest), kontrol negatif (CMC Na 0,5 %), kontrol positif (glibenclamide dosis 1,26 mg/kgBB), ekstrak sirsak 100 mg/kg BB, ekstrak kelor dosis 200 mg/kg BB dan kombinasi I (75:25), II (50:50)dan III (25:75) dalam persen. Semua Kelompok hewan uji, kecuali kelompok normal diinduksi aloksan dosis 150mg/kgBB pada hari ke-0, dilanjutkan dengan perlakuan hewan uji dari hari ke-1 sampai hari ke-14. Dilakukan pengambilan sampel darah pada hari ke-0, 7, dan 14 untuk anallisis kadar gula darah dan selanjutnya ditentukan besar % daya hipoglikemik. Penggunaan ekstrak daun kelor dan sisrsak baik itu tunggal dan kombinasi mampu menurunkan kadar glucose darah. Aktivitashipoglikemik optimal pada kombinasi sirsak kelor 50:50 dengan aktivitas hipoglikemik 36,56 %. Kombinasi ini memeberikan hasil yang lebih bagus dibandingkan bentuk tunggalnyaKata kunci : Sirsak, Kelor, Diabetes Mellitus, aloxan